The Concept of Greater Europe from Lisbon to Vladivostok: Problems and Perspectives - E. Yu. Il’In (Vestnik MGIMO-Universiteta)
The following article deals with the formation and perspectives of the concept of Greater Europe from Lisbon to Vladivostok, and the difficulties in the way of its realization. The author speaks about close historical and cultural ties connecting Russia and Europe, outward and mental resemblance of the peoples of Europe, including Russians.For the first time the theory of Greater Europe was considered in the works of geopoliticians of the beginning and the middle of the twentieth century. It is reflected in the plans to form a pan-European union, drawn by Charles De Gaulle and Michail Gorbachev. Analyzing the statements of modern Russian and European politicians one may come to the conclusion that both parties are mutually interested in the realization of the concept of Greater Europe. However, according to actual evidence, neither Russia, nor the European Union takes any decisive steps in getting closer. The article focuses on serious contradictions between Russia and the European Union on the basic principles underlying Greater Europe. The opposing views refer to the problems of equality in the sphere of strategic partnership, the energy dialogue and the construction of the post-Soviet territory. The author lays stress on the phenomenon of «integrations collision». The article also deals with the destabilizing role of the USA and some European states which actively promote the initiative of the «Eastern partnership». The Ukrainian crisis has become a major strength test in the relations between Russia and the European Union, which resulted in a vast credibility gap, the «war of sanctions», the disruption of business and political ties. Notwithstanding the complexity of the situation, calls for tightening up the connections between the European and Eurasian integration projects are becoming louder. This gives us hope that both parties will not only be able to keep historical ties, but also take steps in creating a common area from Lisbon to Vladivostok.